Autism and intellectual disability in a patient with two microdeletions in 6q16: a contiguous gene deletion syndrome?. Issue 1 (December 2016) - Strunk, Daniela; Weber, Peter; Röthlisberger, Benno; Filges, Isabel
Abstract Background Copy number variations play a significant role in the aetiology of developmental disabilities including non-syndromic intellectual disability and autism. Case presentation We describe a 19-year old patient with intellectual disability and autism for whom chromosomal microarray (CMA) analysis showed the unusual finding of twode novo microdeletions in cis position on chromosome 6q16.1q16.2 and 6q16.3. The two deletions span 10 genes, includingFBXL4, POU3F2, PRDM13, CCNC, COQ3 andGRIK2 . We compared phenotypes of patients with similar deletions and looked at the involvement of the genes in neuronal networks in order to determine the pathogenicity of our patient's deletions. Conclusions We suggest that both deletions on 6q are causing his disease phenotype since they harbour several genes which are implicated in pathways of neuronal development and function. Further studies regarding the interaction betweenPRDM13 andGRIK2 specifically may be interesting.